Effects of poly‐ and monodisperse surfactants on14C‐epoxiconazole diffusion in isolated cuticles of Prunus laurocerasus. Issue 4 (9th October 2012) - Gutenberger, Andrea; Zeisler, Viktoria V; Berghaus, Rainer; Auweter, Helmut; Schreiber, Lukas
Abstract Background Surfactants are known to enhance the foliar uptake of agrochemicals. It was the aim of this study to compare the enhancing effect of three polydisperse surfactants (Brij 30, Plurafac LF300 and Wettol LF700) and five monodisperse alcohol ethoxylates (C12E3, C12E4, C12E5, C12E6 and C12E8) on 14C‐epoxiconazole diffusion in cuticles isolated from cherry laurel (Prunus laurocerasus L.). Results Rate constants (k*) of 14C‐epoxiconazole diffusion were measured in the presence and in the absence of the surfactants. Polydisperse surfactants increased the rates of foliar penetration of 14C‐epoxiconazole by factors of between 8 and 16. With monodisperse surfactants, enhancing effects on cuticular penetration were 2–16‐fold. Effects were highest with alcohol ethoxylates of intermediate size, whereas they were lower for the smaller, more lipophilic and the larger, more polar monomers. In addition, diffusion of four monodisperse alcohol ethoxylates (C12E3, C12E4, C12E5 and C12E6) across cuticles was measured. Rate constants of alcohol ethoxylates decreased with decreasing lipophility and increasing molecular weight. Conclusion The results indicate that enhancement of foliar penetration across cuticles by surfactants was most efficient when both 14C‐epoxiconazole and surfactants had similar mobilities in the transport‐limiting barrier of the cuticles. This observation should be of interest in future strategies to optimise foliar uptake of agrochemicals using surfactants.